What about -- science & technology? - "Parker, Steve" (Miles Kelly Essex, 2011)
In this question and answer book, the answers are provided in the top two-thirds of the spread, with text, illustrations, photographs, and diagrams, while the panel in the lower third provides background information as charts, tables, and images.